Learning by drawing: understanding the potential of comics-based courses in medical education through a qualitative study - Veronica Moretti; Alice Scavarda; Michael J. Green (BMC Medical Education)
Abstract In recent years, medical educators have increasingly incorporated comics into their teaching to promote humanism and empathy and to encourage reflective practice. However, it remains unclear how and to what extent comics-based courses effectively address persistent challenges in medical education, such as the need for more engaging, multimodal learning strategies and the cultivation of emotional intelligence alongside clinical competencies. The aim of this study is to investigate the experiences of students who have enrolled in courses on comics and medicine during medical school. Students in North America who had taken such a course during the previous 5 years were invited to participate in an interview about their experiences. 17 students from 10 different medical schools in North America were interviewed. To explore the students’ views on the value of such courses to their medical education, we used a constructivist grounded analytic approach, employing thematic analysis to understand and interpret our interview. Students reported that comics-based courses support key aspects of their medical training that traditional pedagogical approaches may overlook, such as fostering self-reflection, enhancing empathy, and encouraging creative engagement with complex medical narratives. Moreover, comics contributed to their individual and collective professional identity formation by providing a space for introspection and shared discourse.